2019
DOI: 10.26717/bjstr.2019.18.003125
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Respiratory Symptoms among Woodworkers in Jimma Town, Southwest Ethiopia, A Comparative Cross-Sectional Study

Abstract: Background: Wood dust is one of the most common sources of occupational exposures in the world. Objective:The aim of the present study was to assess respiratory symptoms among woodworkers of Jimma town, Ethiopia, 2018 G.C. Materials and Method:A community based comparative cross-sectional study was conducted among woodworkers and non-woodworkers in Jimma town, 2018 G.C. Multistage random sampling technique was used to select the exposed study group and convenience sampling technique was used to select the non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…This is supported by the personal sampling of the study sites that showed concentrations of total wood dust clearly over TLV set by ACGIH [31] that obtained from working sites with a clear absence of any form of dust control mechanism in place and the proper type of RPE. This finding is comparatively higher than the study done in Southwest Ethiopia, Jimma town with cough (41.4%), phlegm (34.3%), wheezing (12.4%), chest pain (32.9%) and breathlessness (21.5%) [11], a study done in Northeast of Thailand with cough (18.8%), phlegm (15.7%), wheezing (5.9%), and breathlessness (7.8%) [7] and a study done in Ethiopia with cough (39%), phlegm (27%), wheezing (45%), and breathlessness (24%) [13]. The difference might be due to a higher percentage (24.1%) of workers were wearing masks while working and workers had a high level of knowledge and attitude toward dust prevention in the previous studies [7].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…This is supported by the personal sampling of the study sites that showed concentrations of total wood dust clearly over TLV set by ACGIH [31] that obtained from working sites with a clear absence of any form of dust control mechanism in place and the proper type of RPE. This finding is comparatively higher than the study done in Southwest Ethiopia, Jimma town with cough (41.4%), phlegm (34.3%), wheezing (12.4%), chest pain (32.9%) and breathlessness (21.5%) [11], a study done in Northeast of Thailand with cough (18.8%), phlegm (15.7%), wheezing (5.9%), and breathlessness (7.8%) [7] and a study done in Ethiopia with cough (39%), phlegm (27%), wheezing (45%), and breathlessness (24%) [13]. The difference might be due to a higher percentage (24.1%) of workers were wearing masks while working and workers had a high level of knowledge and attitude toward dust prevention in the previous studies [7].…”
Section: Discussioncontrasting
confidence: 57%
“…Chronic respiratory health symptom is one of the major health problems of woodworkers resulting from breathing in noxious or toxic chemicals such as wood dust [6,7]. Wood dust, which is an organic dust, is one of the most occupational exposure woodworkers are exposed during work causing several respiratory diseases [8]. Wood dust is classified as a human carcinogen by the International Agency for Research on Cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whistling breathing during the respiratory cycle perceived by the respondents at least 3 months in a year. 19…”
Section: Methodsmentioning
confidence: 99%
“…Whistling breathing during the respiratory cycle perceived by the respondents at least 3 months in a year. 19 Past respiratory illness. Respiratory disease such as TB, chronic bronchitis, lung cancer, and heart disease that could be developed before and identified by physicians.…”
Section: Operational Definitionmentioning
confidence: 99%